Simulation of Fluid Flow Through Sedan Car YRS 4 Doors with Speed Variation using CFD - Ilmi, Syamsuri; Lillahulhaq, Zain; Yusron, M (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Aerodynamic forces that occur around the vehicle must be considered since it involves safety, ergonomic, and fuel consumption. To reduce fuel consumption, the vehicle should be built as aerodynamic as possible to minimize drag forces. The vehicle becomes unstable at high speed due to increasing lift force. To balance the vehicle at high speed, a downforce should be generated to keep the tires attached to the road surface. Each type of car has a various value of aerodynamic force due to its design, dimension, and cross-section area. The characteristics of streamflow around the car are discussed in this paper. This research simulated 2D sedan car YRS 4 Doors in the steady condition in various velocities, i.e. 23 m/s, 26 m/s, and 40 m/s. This simulation used the Quad Pave mesh model and run in k-Îµ implicit turbulence model. The characteristics could be observed from the qualitative and quantitative data. The quantitative data used as measurable data were Coefficient of Pressure (CP) and Drag Coefficient (CD).Â Quantitative data was shown to outline a better visual explanation of the streaming characteristic. The qualitative data used in this paper are path lines, velocity vectors, and contours. The high-velocity stream results in a low value of CP. When the fluid flowed at high speed through a surface, it had low pressure. The coefficient of drag in the high-speed car decreased as the free stream increased. The value of the coefficient of drag (Cd) from this research was app. 0.567.